2004
DOI: 10.1111/j.1524-4725.2004.30010.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of In Vitro Hair Shaft Elongation in Follicles Stored in Buffers That Prevent Follicle Cell Apoptosis

Abstract: Our study demonstrated an important role of ACD in micrograft transplantation surgery. Preconditioning of micrografts with storage buffers containing inhibitors of ACD could prevent serum-induced ACD after transplantation and might increase the viability of micrografts and the clinical outcome in micrograft transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Since Krugluger et al 2 as described the presence of apoptosis and Crisóstomo 3 revealed the relevance of oxidative stress in hair transplant grafts, the ingredients BMOV and monohydroxy ethylrutoside could have beneficial effects on the viability of the grafts. Lebeau et al 8 and Ortolani et al 9 revealed that different flavonoids, such as rutosides, have beneficial effects on ischemia and reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Krugluger et al 2 as described the presence of apoptosis and Crisóstomo 3 revealed the relevance of oxidative stress in hair transplant grafts, the ingredients BMOV and monohydroxy ethylrutoside could have beneficial effects on the viability of the grafts. Lebeau et al 8 and Ortolani et al 9 revealed that different flavonoids, such as rutosides, have beneficial effects on ischemia and reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…2 Crisóstomo 3 described the presence of oxidative stress in hair transplants. These studies showed that hair transplantation grafts are vulnerable, but do not reveal that in conventional hair transplantation procedures, the preservation solution is essential, since grafts, usually stored for a minimum period of 2 hours in saline solution before implantation, will regenerate new hairs.…”
mentioning
confidence: 99%
“…Studies by Krugluger et al have shown that using antioxidants and various buffers can markedly reduce shedding of transplanted hair post-operatively, and growth is improved. 35 …”
Section: Donor Area Challengesmentioning
confidence: 99%
“…Krugluger et al . [13] demonstrated a dramatic rise in cytoplasmic histone-associated DNA fragments (cHADF) after 36 h of culture in serum-containing DMEM culture media. In addition, cHADF was significantly reduced by storage in media containing antioxidants.…”
Section: Ischaemia–reperfusion Injurymentioning
confidence: 99%
“…Krugluger[18] found that grafts stored for 5 h in DMEM with AMG at 10 µg/mL resulted in a significant increase in HSE. AMG added to PBS showed no effect.…”
Section: Ischaemia–reperfusion Injurymentioning
confidence: 99%